Vector droop line compensation analysis - Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
For sharing of reactive contribution between large generators, a droop line is used, which makes the contribution from a given generator roughly proportional to its device rating. This concept is also useful for control of real and reactive power for microgrids. When the aim is to control balance, fundamental voltage as well as harmonics, the concept of droop lines needs to move to a vector definition. This paper shows how the droop concept can be used to share real and reactive compensation as well as unbalance and harmonic compensation.